2004
DOI: 10.1111/j.0092-5853.2004.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Authority, the Personal Vote, and Budget Discipline in Latin American and Caribbean Countries

Abstract: Patrik MarierÉcole nationale d'administration publique, MontréalRecent scholarship on budgeting in Latin American and Caribbean (LAC) countries indicates that political institutions impact the level of budget discipline. Building upon this previous research, we argue that the principal problem that must be addressed in both the government and the legislature to insure strong fiscal discipline is the common pool resource (CPR) problem. At the cabinet level, the CPR problem arises because ministers consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 40 publications
0
60
0
6
Order By: Relevance
“…The structure of the budget process can help alleviate exploitation of the common pool of state revenue. Numerous studies have demonstrated that a centralized budget process is more effective at lowering aggregate spending levels than a decentralized system (Brady and Morgan 1987;Cogan 1994;Crain and Muris 1995;Hallerberg and Marier 2004;Velasco 1999). For example, Cogan (1994) and Brady and Morgan (1987) find that federal spending began to rise when the number of congressional committees with control over spending decisions increased.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the budget process can help alleviate exploitation of the common pool of state revenue. Numerous studies have demonstrated that a centralized budget process is more effective at lowering aggregate spending levels than a decentralized system (Brady and Morgan 1987;Cogan 1994;Crain and Muris 1995;Hallerberg and Marier 2004;Velasco 1999). For example, Cogan (1994) and Brady and Morgan (1987) find that federal spending began to rise when the number of congressional committees with control over spending decisions increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent papers (e.g., Alesina et al 1999;Filc and Scartascini 2004;Gleich 2003;Hallerberg and Marier 2004;Stein, Talvi, and Grisanti 1998;von Hagen 1991;von Hagen and Harden 1995) have shown that the institutions organizing the budget process have an impact on budget balances: "hierarchical," as opposed to "collegial" budget institutions lead to lower deficits (higher balances). If it is true that presidents have a stronger incentive than prime ministers to keep control over the budget, budget institutions should be, on average, more "hierarchical" in presidential than in parliamentary systems because it is through these institutions that presidents will be able to control the budget (Hallerberg and Marier 2004).…”
Section: Presidential Powers and Budget Balancesmentioning
confidence: 99%
“…5 For empirical tests of this argument, see, for example, Persson et al (2007), de Sturm (1994, 1997), Sakamoto (2001, Hahm et al (1996), and Woo (2003). 6 For empirical tests of the effects budgetary institutions on fiscal outcomes, see de Haan and Sturm (1994), de Haan, Moessen and Volkerink (1999), Leachman et al (2007), Helland (2000), Lagona and Padovano (2007), Alesina et al (1999), Fabrizio and Mody (2006), Filc and Scartascini (2005), Berger et al (2007), Hallerberg and Marier (2004), and Perotti and Kontopoulos (2002). Eur J Law Econ (2010) 30:201-221 205 rarely been mentioned in studies of budgetary commons, despite their common conceptual origins.…”
Section: The Metaphor Of Budgetary Commons In the Existing Literaturementioning
confidence: 99%
“…Also, the incentives provided by the electoral systems are likely to mediate the effects that the size of governing majority may have on budgetary decision-making. In electoral systems where the cultivation of personal vote is prevalent (see, for example, Hallerberg and Marier 2004;Grofman and Reynolds 2001), fiscal discipline may be more difficult to maintain than in systems with stronger party discipline. 18 In sum, as mentioned above Ostrom (1986Ostrom ( , 2005Ostrom ( , 2007 repeatedly 16 Hence, in analysing the distributive politics on legislative budgetary commons, an important question is: Would distributive politics be characterised by minimum-winning coalitions or universalistic coalitions?…”
Section: The Pitfalls Of the Law Of 1/nmentioning
confidence: 99%
See 1 more Smart Citation